QT interval prolongation associated with sibutramine treatment - Harrison-Woolrych, Mira (Blackwell Publishing Ltd, 2006)
AIMS: To investigate a possible association of sibutramine with QT interval prolongation. METHODS: Post-marketing surveillance using prescription event monitoring in the New Zealand Intensive Medicines Monitoring Programme (IMMP) identified a case of QT prolongation and associated cardiac arrest in a patient taking sibutramine for 25 days. This patient was further investigated, including genotyping for long QT syndrome. Other IMMP case reports suggesting arrhythmias associated with sibutramine were assessed and further reports were obtained from the World Health Organisation (WHO) adverse drug reactions database. RESULTS: The index case displayed a novel mutation in a cardiac potassium channel subunit gene, KCNQ1, which is likely to prolong cardiac membrane depolarization and increase susceptibility to long QT intervals. Assessment of further IMMP reports identified five additional patients who experienced palpitations associated with syncope or presyncopal symptoms, one of whom had a QT(c) at the upper limit of normal. Assessment of reports from the WHO database identified three reports of QT prolongation and one fatal case of torsade de pointes in a patient also taking cisapride. CONCLUSIONS: This case series suggests that sibutramine may be associated with QT prolongation and related dysrhythmias. Further studies are required, but in the meantime we would recommend that sibutramine should be avoided in patients with long QT syndrome and in patients taking other medicines that may prolong the QT interval.